“EU CANTO PRA SÃO JOÃO E TU PRA PAJÉ”: uma análise da construção de religiosidades nas toadas de Bumba Meu Boi Sotaque de Matraca (Ilha) - Silva Filho, Marcelo Nicomedes dos Reis (2021)
There is Bumba meu boi in many Brazilian states, sometimes with that name or with variations, such as Cavalo Marinho in Paraíba, Boi de Papao in Santa Catarina, Boi Calemba in Rio Grande do Norte, Bumba de Reis in Espírito Santo and Amazonas and Pará , like Boi-Bumbá. In Maranhão, Bumba meu boi has peculiarities that are not seen in other states, such as the division by styles or, as the Maranhenses call it, accents. These Accents are intended to organize the diversity of Bumba meu boi. The divisions are made taking into account musical rhythm, clothing, characters and way of presenting themselves, establishing the division into five main accents which are: Matraca (Island), Guimarães (Zabumba), Baixada (Pindaré), Costa de Mão and Orchestra. Taking into account the Boi's connection with religion, more specifically the Matraca accent. Our research has as general objective to analyze how relationships, incorporations and conflicts build, discursively, religiosities in the groups of Bumba meu boi do Maranhão, in Sotaque de Matraca (Ilha). We used as a criterion for choosing the corpus, the songs and a documentary, which are materialities with which the discourse materializes in our research, through the intersection of audiovisual and linguistic. Thus, we chose to analyze the material of the three main groups of Bumba meu boi with the Matraca accent: Maioba, Maracanã and Ribamar. Our choice was because it is, among the accents, the one with very strong Indian and black traits. However, the presence of white culture composes the constitution of this accent, and this moves subjects and senses through the play of forces that constitutes the construction of religiosities in Bumba meu boi. We divided the discursive sequences into three main groups and a secondary group. In the main group are the tunes of Bois da Maioba, Maracanã and Ribamar, in the secondary group, tunes from other accents, as well as discursive sequences from other materials such as poems and lyrics that corroborate so that we can demonstrate regularities, approximations and distances between the discourses that cut across those significant materialities. The division was organized as follows: SD(n)Maioba, SD(n)Maracanã and SD(n)Ribamar, for the main group, for the secondary group, SD(n)Others, where we have discursive sequences of the type SD1Maioba, SD2Maracanã and SD3Ribamar. The numerical sequence follows chronologically, changing only the identification of the Ox to which it belongs, as they are all of the same accent, in the first group. In the secondary group, it follows the ascending order (SD4Outros), where Others is related to the tunes of other accents and texts that complete the corpus of analysis. To analyze this heterogeneous corpus, we rely on the Pecheutian Discourse Analysis. Thus, we mobilize some categories of analysis such as ideology, memory, interdiscourse, discursive formation, ideological formation, among others. Therefore, we rely mainly on the researches of Pêcheux (1993, 1995, 2002, 2009, 2010, 2011, 2017), Orlandi (2007, 2011, 2012, 2015), Indursky (2011, 2013), Mariani (1998) , in addition to other authors who follow this same epistemological line.